DIGITALE LEHR- UND LERNMITTEL ZWISCHEN ANZIEHUNGSKRAFT UND WIRKSAMKEIT / English Title: DIGITAL TEACHING AND LEARNING TOOLS BETWEEN ATTRACTIVITY AND EFFECTIVENESS - Andrea Hamburg (Journal of Languages for Specific Purposes)
In the last decades all over the world emerged different trends and approaches in education in general, thus in teaching foreign languages too. New times are likely to need also new teaching methods, young people of this millennium put teachers in front of new challenges. Little by little, digitalisation becomes unavoidable, for the young generation even natural. Thus, in this study we would like to find out, how they use artificial intelligence (AI) if at all and above all if digital teaching and learning tools lead to more student engagement and effectiveness. As this issue, as far as we know, has not been researched in case of Romanian Economics students yet, the originality of this study resides in wanting to give an insight into this matter. The research methodology applied for this reason consists of an anonymous survey related to the abovementioned topics and of an experiment conducted in the summer term of the academic year 2023-2024 among first year students of the Faculty of Economics at the University of Oradea. Those taking part in the experiment were assigned to a control and an experimental group, respectively, where the same language issues – gender of the noun and vocabulary to the topic food names – were dealt with by means of traditional on one and digital tools on the other hand. To check retaining the staff drilled, students of both groups – for reasons of comparability in approximately the same number – had to take short nongraded tests. Variables possibly influencing the results: like previous experience with German language, willingness and capacity to learn, materialised in the grades of the previous term, were also taken into consideration. From the three hypotheses formulated at the beginning, our research produced clear-cut answers only to that related to knowing and using AI by the young generation and to their priority concerning teaching methods and tools. Our first supposition was confirmed, the second one, contrary to expectancy, not validated while in lack of plain, relevant results, the third one related to increased effectiveness of digital teaching and learning tools still remains undecided offering space for extended studies.